Role Implementation of Regional Supervisory Council in the Context of Guidance and Supervision of Notaries - Alfani, Safri Sendi; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The purpose of this research is to analyze and find out: 1). The role of the Regional Supervisory Council (MPD) of Central Lampung Regency in the implementation of guidance and supervision of Notaries. 2) Obstacles and solutions for the Regional Supervisory Council of Central Lampung Regency in the implementation of guidance and supervision of Notaries. The approach method in this research is empirical juridical. The data used are primary and secondary data obtained through interviews and literature study, data analysis was carried out by analytical descriptive. The results of the research concluded: 1). The role of the Regional Supervisory Council (MPD) of Central Lampung Regency in the implementation of guidance and supervision of Notaries is based on the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number M.39.PW.07 of 2004 as referred to in Article 70 and Article 71 of the UUJN, and Article 13 paragraph (2), Article 14, Article 15, Article 16 and Article 17. Several efforts have been made by the MPD of Central Lampung Regency in maximizing its role in providing guidance and supervision of Notaries in its area, namely: with coaching carried out in the form of workshops and routine socialization . As well as implementing preventive and curative supervision. 2). The obstacles for the MPD of Central Lampung Regency in the implementation of guidance and supervision of Notaries.